Italy - a study case of medicines pricing and reimbursement - Valdete A. MELO; Bruna O. ASCEF; Fabrizio GIANFRATE (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2022)
The Italian National Health Service (Servizio Sanitario Nazionale, SSN) is structured at comprehensive levels such as collective prevention and public health, cure and rehabilitation assistance, and pharmaceutical services, with the primary objective of guaranteeing universal access of all Italian citizens, on equal terms, to equitable provision of health services. Italy was used as a case study to explore their healthcare system and their economic regulation and reimbursement of pharmaceuticals. The Italian Medicines Agency (Agenzia Italiana del Farmaco, AIFA) is responsible for regulation related to efficacy, safety and quality, pricing and negotiations for reimbursement of medicines. Among the various negotiation criteria defined in specific legislation, biosimilars and generics enter the Italian market with a discount of at least 20% to the reference medicine. Price review occurs in a periodical basis and upon the emergence of new evidence of efficacy and safety arising from pharmacovigilance or upon request of changes in the therapeutic indications and/or dosage. In addition, conducting the monitoring and analysis of pharmaceutical consumption and expenditure contributes for planning health policy interventions, since it allows for prompt identification of emerging phenomena, framing prescription behaviours, and verifying the effectiveness of regulatory interventions at regional and national levels. Efficacy, safety, and cost-effectiveness analyses are conducted before the introduction of the medicines in the Italian market. It continues to be performed when the drug in on the market with health technologies assessment, constituting a process of permanent investigation of the clinical, economic and social consequences of the medicine's utilisation. In addition, it allows controlling expenses and identifying avoidable costs.